Analysis of Peaceful Commandments in the Medinan Surahs - AlHanaf, Ihab Ahmed; Sotoudehnia, Dr. Mohmmad Reza (Thi Qar Arts Journal, 2024)
Peace, although a contemporary title in Islamic thought and concept, is an ancient concept that has taken a very large and wide space in the thinking of Muslim researchers and scholars, their civilization, and their heritage. Every researcher and scholar, when researching the topic of peace, must stand on the truth of “peace” or “salam.” Although the truth of peace is broader, more widespread, and more common as it is the first message of Islam, “peace” is no less important than “salam.” Islam did not call for peace or salam falsely, playfully, or merely as a slogan, but it is an Islamic truth that calls for freedom, tolerance, and liberation. It never incited war and fighting, nor did it ever support the violation of sanctities and the shedding of blood, as other religions do by inciting and supporting the process of shedding and violating and boasting about killing the soul that God has forbidden to kill, making that a strength and achievement for them. Praise be to God, from the educational and moral policy of Islam in wars, it never started war and fighting at all. All wars and battles during the time of the Prophet (peace be upon him) were defensive. Islam never went to wage war on the infidels out of pride, arbitrariness, and challenge. Researchers and scholars have mentioned that Islam did not start war and fighting except in the morning. It is mentioned in one of the battles when the polytheists attacked at night and were repelled, the Muslims did not attack them by the order of the Commander of the Faithful (peace be upon him). Also, our noble Prophet (peace be upon him) used to advise Muslims before fighting not to kill the elderly, the young boys, and women, and to prevent mutilation of bodies and treachery, and that killing should be purely for the sake of God Almighty. This is the educational and humanitarian policy of Islam.